Buccal health in asthmatic patients. - Nora Sexto Delgado; Aracelis Navarro Sánchez; Mabay Ocampo Sexto; Joel González Beriao (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2003)
Background: Buccal health as integral and determinant part of general health makes us find different ways and methods to elevate life quality in the population. Objective: To establish the risk of suffering from dental cavities in asthmatic patients. Methods: A non match case and control study constituted by 100 children selected at simple random from the universe of asthmatic patients belonging to the General Comprehensive doctor offices number 7,9,10, 11, 43, and 44 from Area II in Cienfuegos municipality. The controlled group was selected in the same offices but from the universe of non asthmatic children. The age in both groups was from 6 to 15 years old. Visits to the children´s home were carried out for the record of the information through health oral dental and buccal health knowledge surveys. Results: The index of cavities, lost, and obturated permanent teeth was higher (3, 28) than in the control group (0, 44). The buccal hygiene indexes and the level of knowledge in both groups did not show significant differences. The most used drugs in asthma therapy were salbutamol and ketotifeno which change the buccal milieu. The odds ratio technique between asthmatic and non asthmatic patients showed 4, 9 times more at risk of suffering from dental cavities in the first group. Finally, it can be stated that the asthmatic patients are more at risk of suffering from cavities than the non asthmatic ones, so a program for buccal health in these patients should be performed.